Data positioning as an instrument of constructive data compression - Kasumov, N. K. (Automatic control and computer sciences, 2012)
A fundamentally new algorithm for data compression is considered. A theoretical basis is provided for the formation, modification, and conversion of data positions aimed at their reversible compression. The specifics are described of a method development based on structure encryption, i.e., reformatting the architecture of the compressed data alphabet based on the positionality and conditionality properties of the compression level and the structural numbering of the reformatted alphabet’s architecture in a positional multilevel space. We substantiate the principle of redundancy reduction due to the following: the simultaneous modification of the positions inhibiting the appearance of noninteger values of new positions and constraints on the digit capacity of the elements in positioning arrays, the identification of the carriers of stabilizing elements in the digital space, and the reduction of the positions with code combinations in the course of the array processing. A particular case of a data conversion protocol is presented. Problems are solved of combining the principles of data reversibility and supercompression both in the modes of single and multiple use of one and the same encryption scenario. The cost of the positioning processes and their influence on the efficiency of the processes of the data encoding and decoding have been determined.